Multimodality in higher education - Archer, Arlene; Breuer, Esther Odilia, 1971- (Studies in writing, 2016)
Multimodality in Higher Education theorizes writing practices and pedagogy from a multimodal perspective. It looks at the theoretical and methodological uptake of multimodal approaches in a range of domains in Higher Education, including art and design, architecture, composition studies, science, management accounting and engineering. Changes in the communication landscape have engendered an increasing recognition of the different semiotic dimensions of representation. Student assignments require increasingly complex multimodal competencies and Higher Education needs to be equipped to students with these texts. Multimodality in Higher Education explores the changing communication landscapes in Higher Education in terms of spaces and texts, as well as new processes of production and creativity in the new media.